2013
DOI: 10.1016/j.dnarep.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair mechanisms in dividing and non-dividing cells

Abstract: DNA damage created by endogenous or exogenous genotoxic agents can exist in multiple forms, and if allowed to persist, can promote genome instability and directly lead to various human diseases, particularly cancer, neurological abnormalities, immunodeficiency and premature aging. To avoid such deleterious outcomes, cells have evolved an array of DNA repair pathways, which carry out what is typically a multiple-step process to resolve specific DNA lesions and maintain genome integrity. To fully appreciate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
554
1
29

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(591 citation statements)
references
References 263 publications
(271 reference statements)
7
554
1
29
Order By: Relevance
“…Using this cutoff value, a total of 433 siRNAs were identified that potentially sensitize SW1575 to radiation (Supplementary Table S1). Interestingly, several genes involved in the DNA damage response were amongst these hits, such as RAD51, TOPBP1, HTATIP, RNF168, PNKP, and TRIM28 (15)(16)(17)(18)(19). A more detailed pathway analysis of the hits using Ingenuity Pathway Analysis software (www.ingenuity.com) showed that proteins belonging to specific cellular functions, such as cell-cycle control as well as cell death and survival, were significantly overrepresented in the hit list ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Using this cutoff value, a total of 433 siRNAs were identified that potentially sensitize SW1575 to radiation (Supplementary Table S1). Interestingly, several genes involved in the DNA damage response were amongst these hits, such as RAD51, TOPBP1, HTATIP, RNF168, PNKP, and TRIM28 (15)(16)(17)(18)(19). A more detailed pathway analysis of the hits using Ingenuity Pathway Analysis software (www.ingenuity.com) showed that proteins belonging to specific cellular functions, such as cell-cycle control as well as cell death and survival, were significantly overrepresented in the hit list ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…O‐6‐methylguanine‐DNA methyltransferase (MGMT) is an enzyme involved in the direct reversal of DNA damage in vitro and postmitotic cells in vivo by methylating agents used clinically for chemotherapy (Iyama & Wilson, 2013; Jiang et al ., 2014). It have been suggested that MGMT may play a role in regulating mouse lifespan (Meira et al ., 2014), but it is not known whether long‐lived mice, such as Snell, GHRKO, and PAPPA‐KO, have altered expression of MGMT.…”
Section: Introductionmentioning
confidence: 99%
“…Yanlış baz çifti MMR (Mismatch Baz Kesip-Çıkarma Nükleotid Kesip Çıkarma Homolog Rekombinasyon Homolog Olmayan Uç Birleştirme repair) sistemi ile de tamir edilemezse yanlış eşleşmiş bazlar replikasyon sonunda hücrede çift zincir DNA kırıklarının oluşmasına, apoptoz yolağının tetiklenmesine, ayrıca kromozomal anomalilere ve kansere yol açabilir 2,13,15 . Metilasyon ajanlarının hücre DNA'sında oluşturduğu O6-MeG eklentisi, MGMT (O6-metilguanin-DNA-metiltransferaz) isimli bir enzim tarafından tamir edilir ve metilasyon kaldırılır 2,13,16 . MGMT memeli hücre ve dokularında DNA alkilasyon ajanlarının zararlı etkilerine karşı koruyucu bir rol oynamaktadır 11,15 .…”
Section: O6-mgmt Ile Onarımunclassified
“…Endojen faktörler; DNA'da kendiliğinden meydana gelen hatalar olabildiği gibi hücresel metabolizmanın yan ürünü olarak üretilen reaktif oksijen ve nitrojen türleri, lipid peroksidasyon ürünleri, endojen alkilasyon ajanları, östrojen ve kolesterol metabolitleri ve reaktif karbonil türleri de olabilmektedir 1, 2,3 . Ekzojen faktörler ise ultraviole ışığı, iyonize radyasyon, ağır metaller, hava kirliliği, sigara dumanı, kemoterapötik ilaçlar olarak sayılabilmektedir 1, 2,4,5 . Bir memeli genomunda her gün yaklaşık olarak 10 4 'ten daha fazla DNA hasarının ortaya çıktığı tahmin edilmektedir 2,6 .…”
Section: Introductionunclassified
See 1 more Smart Citation